PENGANUT ISLAM DAN DINAMIKA KEBUDAYAAAN DI DESA TUTUMALOLEO KECAMATAN GALELA UTARA KABUPATEN HALMAHERA UTARA PROPINSI MALUKU UTARA - Jamrud, Isnain; Deeng, Djefry; Mulianti, Titiek (Universitas Sam Ratulangi, 2020)
Indonesia is a country with many cultures. The culture has been inherent in society and has been hereditary for a long time, will be more conceptualized in people's lives so that it becomes a belief in matters related to a belief that is difficult to eliminate. With the existence of community culture will be able to understand the religion contained in the empirical plains or religions that appear in the formal form that galvany in society, the development of culture cannot be released from religion. Because the two have a very close relationship between religions is part of the culture.The entry of Islam in Tutumaloleo Village has an impact on cultures that have existed since time immemorial, giving rise to various cultural dynamics. In addition to the entry of Islam there are several factors that contribute to the occurrence of cultural dynamics in the village of Tutumaloleo, these factors come from within the community, outside the community, and environmental factors.The acculturation between local culture and Muslims in Tutumaloleo Village still has a good impact. In this context, they can organize their cultural elements better and keep the local culture side by side with the Islamic teachings embraced by the people in Tutumaloleo Village. In real terms, the community continues to develop but still maintains some local traditions. In addition to the Islamic entry factor, the dynamics and acculturation of local cultures are also affected by the factors of globalization, modernization and the development of the times.Keywords: cultural dynamics, acculturation, maintaining